Corporate social responsibility, work engagement and hospital image: the roles of hospital reputation, organizational trust and information technology application - Hoang Nguyen, Dung; Hai Nguyen, Quang (Business: Theory and Practice, 2025)
This study investigates the mediating role of hospital reputation (HOR), organizational trust (ORT), and the moderating role of perceived usefulness of information technology application (ITA) in the relationship between corporate social responsibility (CSR), work engagement (WOE), and hospital image (HOI). Using survey data from 586 healthcare workers employed at public hospitals in Ho Chi Minh City, Vietnam, the study employs partial least squares structural equation modeling (PLS-SEM) to test the measures and hypotheses. The results reveal that effective CSR practices not only foster a positive work environment and enhance WOE but also significantly improve HOI. HOR and ORT partially mediate the impact of CSR on WOE and, alongside WOE, act as crucial mediators in the CSR-HOI relationship. These findings confirm that organizational reputation and trust are foundational to building sustainable relationships between organizations and employees while also strengthening the hospital’s image in the community. Furthermore, the study identifies perceived usefulness of ITA as a significant benefit that positively modifies the impact of CSR on HOI. From these results, practical managerial implications are proposed for hospital leaders to enhance WOE and HOI through the implementation of CSR and ITA practices.